Cholelithiasis in Infants: Risk Factors, Management, and the Role of Ursodeoxycholic Acid - Sevim Çakar; Gülin Eren; Cahit Barış Erdur; Mehmet Önder; Şafak Pelek; Sedef Alpdoğan; Duygu Demirtaş; Çiğdem Ömür Ecevit; Özlem Bekem (Children)
Background: Cholelithiasis is a rare disease in infants, and there is limited data on its risk factors and management. Objectives: To evaluate the risk factors, management, and response to medical treatment of cholelithiasis in infants. Methods: Infants diagnosed with cholelithiasis by ultrasound between 2018 and 2023 were retrospectively analyzed. Details of patient history, imaging findings, current symptoms, and treatments were reviewed. Results: Over 5 years, 98 infants were diagnosed with cholelithiasis. Thirty-three (33.7%) were girls, and the most common risk factors were the use of cephalosporin antibiotic therapy in 46.9%, sepsis in 30.6%, total parenteral nutrition in 29.6%, prematurity in 27.6%, congenital heart disease in 18.4%, and genetic disease (Down syndrome diagnosis in seven patients) in 16.3%. Only fifteen patients (15.3%) were symptomatic. Ursodeoxycholic acid (UDCA) treatment was given to 90.8% of patients, but nine of them used it for a short period or irregularly, and regular users were 81.6%. Gallstones disappeared in 46 patients (46.9%), including 14 (30.4%) without using UDCA regularly. The response rate to UDCA treatment was lower in preterm infants (p = 0.004). Gallstone resolution was higher in the nonusers, 14/18 (77.8%) versus 32/79 (40.5%) (p = 0.03). Acute cholecystitis was observed in only four patients; no other complications were noted. No infant required surgical or endoscopic treatment. Conclusions: UDCA should not be used routinely in children, especially infants, except in symptomatic children with a contraindication to surgery or to reduce clinical symptoms. In the absence of symptoms, patients may be monitored clinically.